Titanium alloy, preparation method thereof and titanium alloy rod

By mixing the matrix powder containing titanium elements with the reinforced powder of alloy elements and sintering, the problem of insufficient bonding strength and composition uniformity of traditional ceramic particles reinforced titanium-based composite materials is solved, high bonding strength and uniformity are achieved, and processing difficulty and cost are reduced.

CN119553121APending Publication Date: 2025-03-04GOERTEK INC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311297934.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-01
Filing Date
2023-10-08
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Traditional ceramic particle-enhanced titanium-based composites have shortcomings in bonding strength and composition uniformity, resulting in increased processing difficulty and high cost.

Method used

By mixing the matrix powder containing titanium elements with reinforced powder containing alloy elements, including metal elements such as aluminum, vanadium, molybdenum, chromium, iron, and non-metal elements such as carbon, boron, and nitrogen, the titanium alloy containing ceramic phase is carried out to produce a titanium alloy.

Benefits of technology

It improves the bonding strength and composition uniformity of the ceramic phase in the titanium alloy, reduces processing difficulty and cost, and at the same time makes the ceramic phase evenly distributed within the powder particles, improving material performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553121A_ABST
    Figure CN119553121A_ABST
Patent Text Reader

Abstract

The invention provides a titanium alloy and a preparation method thereof and a titanium alloy rod.The preparation method of the titanium alloy comprises the following steps that matrix powder containing titanium elements and reinforcing powder containing alloy elements are mixed to form mixed powder, the alloy elements comprise metal elements and non-metal elements, and the alloy elements comprise metal elements and non-metal elements; the metal elements comprise at least one of aluminum, vanadium, molybdenum, chromium and iron, and the non-metal elements comprise at least one of carbon, boron and nitrogen; the mixed powder is subjected to blank making, and a blank is obtained; and sintering the green body to generate the titanium alloy containing the ceramic phase. According to the technical scheme, the bonding strength and component uniformity of the ceramic phase in the titanium alloy rod can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder metallurgy, and in particular to a titanium alloy, a method for preparing the titanium alloy, and a titanium alloy rod. Background Art

[0002] Titanium alloys have the characteristics of high specific strength, good corrosion resistance, and excellent biocompatibility, and are widely used in aerospace, smart wearables, 3C, automobiles, medical treatment, and chemical industries. Ceramic particle reinforced titanium matrix composites are reinforced by combining one or more ceramic particles with a matrix titanium alloy. They have excellent comprehensive properties such as low density, high strength, high hardness, high specific stiffness, and specific modulus, and have received great attention from the scientific research community and the industry.

[0003] Traditional ceramic particle reinforced titanium-based composite materials are generally made by directly mixing or ball-milling the ceramic phase and then sintering. However, the ceramic particle reinforced titanium-based composite products obtained by this manufacturing method are prone to problems such as low bonding strength between the ceramic phase and the matrix, poor component uniformity, component contamination, and mold wear. At present, the usual method of adding a higher proportion of ceramic particles is to solve the above problems. However, due to the high strength and hardness of ceramic particles, it will increase the difficulty of processing and the cost is high. Summary of the invention

[0004] The main purpose of the present invention is to provide a titanium alloy, a method for preparing the titanium alloy and a titanium alloy rod, aiming to improve the bonding strength and composition uniformity of the ceramic phase in the titanium alloy.

[0005] To achieve the above object, the present invention provides a method for preparing a titanium alloy, the method comprising the following steps:

[0006] Mixing a base powder containing titanium elements with a reinforcing powder containing alloy elements to form a mixed powder, wherein the alloy elements include metal elements and non-metal elements, the metal elements include at least one of aluminum, vanadium, molybdenum, chromium, and iron, and the non-metal elements are at least one of carbon, boron, and nitrogen;

[0007] Forming the mixed powder into a green body to obtain a green body;

[0008] The green body is sintered to produce a titanium alloy containing a ceramic phase.

[0009] In one embodiment of the present application, the mass ratio of each element in the mixed powder is:

[0010] Aluminum 4% to 6%;

[0011] Vanadium 4% to 6%;

[0012] Molybdenum 4% to 6%;

[0013] Iron 0.5% to 1.5%;

[0014] Chromium 0.5% to 1.5%;

[0015] At least one of carbon, boron and nitrogen 0.5% to 1.5%;

[0016] The balance is titanium.

[0017] In one embodiment of the present application, the matrix powder includes at least one of titanium powder and titanium alloy powder.

[0018] In one embodiment of the present application, the step of mixing a base powder containing titanium element and a reinforcing powder containing alloy elements to form a mixed powder comprises:

[0019] Adding a binder to the base powder and the reinforcing powder and heating and mixing them to obtain a mixture; wherein the binder includes at least one of epoxy resin, phenolic resin, and rubber;

[0020] After the mixture is cooled, it is crushed to obtain mixed powder;

[0021] Alternatively, the step of mixing the matrix powder containing titanium element and the reinforcing powder containing alloy element to form a mixed powder comprises:

[0022] Adding liquid to the base powder and the reinforcing powder and mixing them to obtain a mixture; wherein the liquid includes at least one of liquid epoxy resin, liquid phenolic resin, acetone epoxy resin solution, ethyl acetate epoxy resin solution, acetone phenolic resin solution, ethanol phenolic resin solution, ethanol, ethyl acetate, acetone, gasoline rubber solution, engine oil, and gasoline;

[0023] The mixed material is dried to obtain mixed powder.

[0024] In an embodiment of the present application, the mass percentage of the binder to the mixed powder is 0.1% to 5.0%.

[0025] In one embodiment of the present application, the step of forming the mixed powder into a green body to obtain a green body comprises:

[0026] The mixed powder is placed in a bag and subjected to a forming process to obtain a green body.

[0027] In one embodiment of the present application, the step of placing the mixed powder in a bag and performing a forming process to obtain a green body comprises:

[0028] The mixed powder is placed in a bag, and after compaction, the bag is vacuum-sealed to form a green body.

[0029] In one embodiment of the present application, after the step of placing the mixed powder in a bag and performing a forming process to obtain a green body, the step further includes:

[0030] The green body is rotary forged to increase the density of the mixed powder.

[0031] In one embodiment of the present application, the step of rotary forging the blank to increase the density of the mixed powder includes:

[0032] The green body is rotary forged to make the density of the mixed powder reach 80%-98%.

[0033] In one embodiment of the present application, the material of the sheath is titanium.

[0034] In one embodiment of the present application, the step of sintering the green body to generate a titanium alloy containing a ceramic phase includes:

[0035] The sintering temperature is controlled to be 800° C. to 1400° C., the sintering time is 10 min to 120 min, the sintering atmosphere is at least one of vacuum, argon or nitrogen, and the green body is sintered to generate a ceramic phase in situ and to produce a titanium alloy with a density of not less than 95%.

[0036] The present application also proposes a titanium alloy, which is prepared by the method for preparing the titanium alloy in any of the above embodiments, and includes at least one ceramic phase of carbide, boride and nitride. The method for preparing the titanium alloy includes the following steps:

[0037] Mixing a base powder containing titanium elements with a reinforcing powder containing alloy elements to form a mixed powder, wherein the alloy elements include metal elements and non-metal elements, the metal elements include at least one of aluminum, vanadium, molybdenum, chromium, and iron, and the non-metal elements are at least one of carbon, boron, and nitrogen;

[0038] Forming the mixed powder into a green body to obtain a green body;

[0039] The green body is sintered to produce a titanium alloy containing a ceramic phase.

[0040] The present application also provides a titanium alloy rod, which includes the titanium alloy in the aforementioned embodiment.

[0041] In the preparation method of titanium alloy proposed in the present application, a titanium-containing base powder and a reinforcing powder containing at least one element of carbon, boron and nitrogen are mixed to form a mixed powder for sintering. At this time, different elements or compounds can undergo chemical reactions during sintering, and one or more ceramic phases including carbides, borides and nitrides are directly generated in the metal matrix. The ceramic phase generated in the metal matrix in this way has a high bonding strength with the metal matrix and the ceramic phase is evenly distributed. When the titanium alloy is atomized into powder, the ceramic phase is finely dispersed and evenly dispersed inside the powder particles, which is beneficial to improving material properties, so that the prepared powder can meet the use requirements in the fields of pressing, injection molding, additive manufacturing, etc.; the elemental composition of the titanium alloy can also be freely adjusted, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0043] Figure 1 This is a flow chart of a first embodiment of a method for preparing a titanium alloy according to the present invention;

[0044] Figure 2 This is a flow chart of a second embodiment of a method for preparing a titanium alloy according to the present invention;

[0045] Figure 3 is a flow chart of a third embodiment of a method for preparing a titanium alloy according to the present invention;

[0046] Figure 4 is a flow chart of a fourth embodiment of a method for preparing a titanium alloy according to the present invention;

[0047] Figure 5 is a flow chart of a fifth embodiment of a method for preparing a titanium alloy according to the present invention;

[0048] Figure 6 is a flow chart of a sixth embodiment of a method for preparing a titanium alloy according to the present invention;

[0049] Figure 7 is a flow chart of a seventh embodiment of a method for preparing a titanium alloy according to the present invention;

[0050] Figure 8 This is a flow chart of an eighth embodiment of the method for preparing titanium alloy according to the present invention.

[0051] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0054] In the present invention, unless otherwise clearly specified and limited, the terms "connection", "fixation", etc. should be understood in a broad sense. For example, "fixation" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0055] In addition, in the present invention, descriptions such as "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0056] In response to the technical problems raised by the background technology, the present application proposes a method for preparing a titanium alloy, which can improve the bonding strength and composition uniformity of the ceramic phase in the titanium alloy.

[0057] The preparation method of the titanium alloy proposed in this application will be described below with reference to specific embodiments.

[0058] Please refer to Figure 1 In some embodiments of the present application, the method for preparing the titanium alloy includes:

[0059] Step S10, mixing a base powder containing titanium elements with a reinforcing powder containing alloy elements to form a mixed powder, wherein the alloy elements include metal elements and non-metal elements, the metal elements include at least one of aluminum, vanadium, molybdenum, chromium, and iron, and the non-metal elements are at least one of carbon, boron, and nitrogen.

[0060] Specifically, titanium alloy is an alloy material formed by adding other elements to titanium. In this embodiment, a mixed powder is formed by adding reinforcing powders of other required elements to a base powder containing titanium, and the reinforcing powder can be a pure powder or compound powder containing the required alloying element, which is then fused with the titanium base powder by powder metallurgy sintering or the like. The base powder can be one of titanium powder and titanium alloy powder, and the titanium alloy can contain at least one metal element such as aluminum, vanadium, molybdenum, chromium, and iron. At the same time, in order to produce a ceramic phase in the titanium alloy, the mixed material elements should also include at least one non-metallic element of carbon, boron, and nitrogen, so that at least one ceramic phase of carbide, boride, and nitride can be directly reacted in situ during sintering. Among them, for elements such as aluminum, vanadium, molybdenum, chromium, iron, carbon, and boron, pure powders of the elements can be directly added, such as aluminum powder, vanadium powder, molybdenum powder, chromium powder, iron powder, graphite powder, and boron powder, or compounds containing the elements can be added. For nitrogen, it needs to be added and mixed in the form of compound powders, such as titanium nitride, aluminum nitride, vanadium nitride, molybdenum nitride, chromium nitride, and iron nitride. It can be understood that the added material powders containing other elements can also be selected in different mass ratios based on calculations and the required titanium alloy strength or other property requirements, and the composition can be adjusted freely and flexibly.

[0061] In this embodiment, various required powders are mixed in a certain proportion and homogenized to form a powder blank. There are three mixing methods: dry, semi-dry and wet. During the pre-mixing of powders, due to the different specific gravities of particles of different components, segregation will occur during the powder mixing process. In addition, due to the different particle sizes in the powder, uneven distribution can easily lead to increased porosity. In some embodiments, the segregation can be effectively improved by adding a binder, so that the particles are reasonably distributed, the pores are filled, and the strength of the pressed green sheet is improved, so that the components of the final generated titanium alloy are evenly distributed, and the ceramic phase produced is fine and dispersed.

[0062] Step S20, forming a green body by molding the mixed powder.

[0063] Specifically, after the matrix powder and the reinforcing powder are evenly mixed, the mixed powder mixture needs to be pressed to form a green body with a certain shape, size and density. Isostatic pressing, compression molding, extrusion molding or rolling can be used. This can have a predetermined shaping effect on the desired alloy shape, obtain a semi-finished product of a predetermined shape, reduce the powder voids in the green body, and facilitate the molding of higher density titanium alloys.

[0064] Step S30, sintering the green body to generate a titanium alloy containing a ceramic phase.

[0065] Specifically, the blank formed into a rough product shape after forging is sintered, which can cause melting, diffusion, welding, recrystallization and other processes between the blank particles, so that the powder particles are firmly welded together, the pores are reduced, the density is increased, and finally a titanium alloy is obtained. Since the mixed powder contains at least one metal element such as aluminum, vanadium, molybdenum, chromium, and iron, at the same time, in order to produce a ceramic phase in the titanium alloy, the mixed material elements should also include at least one non-metallic element of carbon, boron, and nitrogen, so that a ceramic phase can be directly reacted in situ during sintering. The generated ceramic phase can be at least one of carbide, boride, and nitride according to the elements contained in the pre-added material. In many cases, sintering needs to be carried out in a specific atmosphere or vacuum to avoid oxidation of the titanium alloy and the material, so as to obtain a titanium alloy with a certain structure.

[0066] Therefore, it can be understood that in the preparation method of titanium alloy proposed in the present application, a titanium-containing base powder and a reinforcing powder containing at least one element of carbon, boron and nitrogen are mixed to form a mixed powder for sintering. At this time, different elements or compounds can react chemically during sintering, and one or more ceramic phases including carbides, borides and nitrides are directly generated in the metal matrix. The ceramic phase generated in the metal matrix in this way has a high bonding strength with the metal matrix and the ceramic phase is evenly distributed; when the titanium alloy is atomized into powder, the ceramic phase is fine and dispersed evenly inside the powder particles, which is beneficial to improving the material properties, so that the prepared powder can meet the use requirements in the fields of pressing, injection molding, additive manufacturing, etc.; the elemental composition of the titanium alloy can also be freely adjusted at a low cost.

[0067] In one embodiment of the present application, the mass ratio of each element in the mixed powder is 4% to 6% aluminum; 4% to 6% vanadium; 4% to 6% molybdenum; 0.5% to 1.5% iron; 0.5% to 1.5% chromium; 0.5% to 1.5% of at least one of carbon, boron and nitrogen; and the balance is titanium.

[0068] In this embodiment, the mixed powder includes aluminum, vanadium, molybdenum, chromium, iron and other element materials, and the mass ratio of each element is constrained and limited, wherein the mass percentage of the aluminum element can be 4% to 6%, and can be 4%, 4.1%, 4.5%, 5%, 5.2%, 5.8%, 6% or any value between 4% and 6%, and the mass percentage ranges of the vanadium element and the molybdenum element are respectively 4% to 6%, and can be 4%, 4.1%, 4.5%, 5%, 5.2%, 5.8%, 6% or any value between 4% and 6%. Any value is taken, so that the mass percentage range of iron and chromium elements is 0.5% to 1.5% respectively, and can be 0.5%, 0.6%, 0.8%, 1.0%, 1.3%, 1.31%, 1.5% or any value between 0.5% and 1.5%, which is not limited here. Of course, with the development of manufacturing technology, changes in technology or different mixed alloy elements, such as adding other alloy elements or replacing certain elements, the mass ratio of the above elements can also be made not within the above set range to achieve similar technical effects. For any of carbon, boron and nitrogen, the mass percentage range is 0.5% to 1.5%, which can be 0.5%, 0.6%, 0.8%, 1.0%, 1.3%, 1.31%, 1.5% or any value between 0.5% and 1.5%, and the mass ratio of carbon, boron and nitrogen in the titanium alloy produced is 0.5 to 5.0%.

[0069] In one embodiment of the present application, the matrix powder includes at least one of titanium powder and titanium alloy powder.

[0070] Specifically, pure titanium powder or titanium alloy powder can be used as the base powder. The elements in the titanium alloy powder, in addition to titanium, may include at least one of aluminum, vanadium, molybdenum, chromium, and iron. At this time, it is necessary to calculate and obtain the ratio of the base powder and the reinforcement powder based on the required mass ratio of each element and the mass ratio of each element in the titanium alloy powder to improve the precision control of the finished product composition.

[0071] It is understandable that during the powder mixing process, due to the different specific gravities of particles of different components, segregation may occur during the powder mixing process, and the uneven distribution of particles due to different sizes in the powder may easily lead to an increase in porosity. In some embodiments, the segregation can be effectively improved by adding a binder, so that the particles are reasonably distributed, the pores are filled, and the strength of the pressed green sheet is improved, so that the composition of the final titanium alloy is evenly distributed, and the resulting ceramic phase is fine and dispersed.

[0072] Please refer to Figure 2 In some embodiments of the present application, the step of mixing the matrix powder containing titanium element and the reinforcing powder containing alloy element to form a mixed powder comprises:

[0073] Step S11, adding a binder to the base powder and the reinforcing powder and heating and mixing them to obtain a mixture; wherein the binder includes at least one of epoxy resin, phenolic resin, and rubber;

[0074] Step S13, cooling the mixed material and crushing it to obtain mixed powder.

[0075] In this embodiment, epoxy resin, phenolic resin or rubber is used as a binder, which is melted by heating to become viscous and fluid, and then mixed with the batched powder to form a slurry, and then the slurry is fully mixed to ensure that the various powders are evenly mixed.

[0076] After the binder cools, the powder is bonded into agglomerates by the binder, and the agglomerates are mechanically crushed to form powders. At this time, the powders can be sieved to obtain a uniformly mixed titanium alloy bonding powder mixture with uniform powder particles. The titanium alloy bonding powder mixture is then processed into a blank to obtain a semi-finished blank of a certain shape, size and density, and the blank is sintered. During this process, diffusion, welding, recrystallization and other processes can occur between the particles of the blank, so that the powder particles are firmly welded together and a ceramic phase is generated in situ, thereby obtaining a titanium alloy containing a ceramic phase with reduced porosity and increased density. At the same time, the binder in the mixture can also be removed to obtain the required titanium alloy with higher purity.

[0077] Please refer to Figure 3 In some embodiments of the present application, the step of mixing the matrix powder containing titanium element and the reinforcing powder containing alloy element to form a mixed powder comprises:

[0078] Step S12, adding liquid to the base powder and the reinforcing powder and mixing them to obtain a mixture; wherein the liquid includes at least one of liquid epoxy resin, liquid phenolic resin, acetone epoxy resin solution, ethyl acetate epoxy resin solution, acetone phenolic resin solution, ethanol phenolic resin solution, ethanol, ethyl acetate, acetone, gasoline rubber solution, engine oil, and gasoline;

[0079] Step S14, drying the mixed material to obtain mixed powder.

[0080] In this embodiment, at least one solvent of liquid epoxy resin, liquid phenolic resin, acetone epoxy resin solution, ethyl acetate epoxy resin solution, acetone phenolic resin solution, ethanol phenolic resin solution, ethanol, ethyl acetate, acetone, gasoline rubber solution, engine oil, and gasoline is used as a mixing aid, so that the powders after batching are mixed with the mixing aid to form a mixture, and the mixture is fully mixed to make the various powders evenly mixed; among them, when using resin materials such as liquid epoxy resin and liquid phenolic resin, a curing agent can be added for use in combination.

[0081] The mixture is then dried to evaporate the liquid, thereby obtaining a uniformly mixed powder and ultimately obtaining the desired titanium alloy with a high degree of purity.

[0082] In an embodiment of the present application, the mass percentage of the binder is 0.1% to 5.0%.

[0083] Specifically, the mass percentage of the binder is in the range of 0.1% to 5.0%, and can be 0.1%, 0.5%, 0.6%, 0.8%, 1.0%, 1.3%, 1.31%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.1%, 4.5%, 5% or any value between 0.1% and 5.0%, which is not limited here. Such a setting can avoid excessive binder content leading to excessive pores between the final blanks, and the long distance between the powders making it difficult to obtain a titanium alloy with a higher density; at the same time, it can avoid too low a binder content and the inability to fully mix the powders, ensuring that the powders can be evenly mixed.

[0084] In one embodiment of the present application, the step of adding a binder to the base powder and the reinforcing powder and mixing them comprises:

[0085] The base powder and the reinforcing powder are placed in a mixer and mixed for 0.5 to 1 hour, and then a binder is added and mixed for 0.5 to 1 hour to form a bonding powder.

[0086] In this embodiment, a mixer is used to mix the powder and the binder to reduce manual operation and facilitate uniform mixing of the material powders. The base powder and the reinforcing powder are first stirred in the mixer for a certain period of time to allow the powders to be preliminarily mixed, and then the binder is added to the mixture to avoid the material powders of the same material from agglomerating and failing to be fully mixed when the binder is initially added.

[0087] Please refer to Figure 4 In one embodiment of the present application, the step of forming the mixed powder into a green body to obtain a green body comprises:

[0088] Step S21, placing the mixed powder in a package and performing a forming process to obtain a green body.

[0089] Specifically, the mixed powder is put into a sheath, and the mixed powder is shaped by the sheath, and then the mixed powder is densified by knocking, vibration or other means, and the density is increased to the required range as required. Since the powder is uniformly compressed in all directions in the sheath, a green body with relatively uniform density can be obtained, and it is not easy to deform and crack during sintering; the sheath can be set into different forms according to the titanium alloy structure to be formed in the end, for example, it can be made into a tube, a rectangular tank, a cube tank, a prismatic tank or other regular or irregular structures, and the sheath can be made of materials such as stainless steel, ceramic or titanium, which are not limited here. In some embodiments, the sheath material can be removed after sintering to obtain a relatively pure titanium alloy material. Of course, a thinner titanium tube can be directly used as the sheath material, and the powder density in the mixed powder can be increased, so that the elemental composition of the titanium alloy reaches the required component ratio without removing the titanium sheath.

[0090] Please refer to Figure 5 In one embodiment of the present application, the step of placing the mixed powder in a bag and performing a forming process to obtain a green body includes:

[0091] Step S211, placing the mixed powder in a package, and after compaction, vacuum sealing the package to form a green body.

[0092] Specifically, after the powder materials are mixed evenly, the mixed powder is put into the bag, and then the mixed powder is vibrated to make the powder materials stacked as tightly as possible to reduce the air mixed between the mixed powders. The titanium tube is then evacuated and the bag is sealed to expel the air in the bag, thereby further making the powder full and tight in the bag and improving the density of the green body. At this time, when sintering is performed, the problem of oxidation of the titanium alloy due to the presence of air in the bag can be avoided, thereby improving the cleanliness of the generated titanium alloy.

[0093] Preferably, in some embodiments, according to the selected titanium tube size and the preset material ratio, the mixed powder is filled in the sleeve, and after the vibration and vacuum sealing operation, the density of the obtained blank is 40%-70%, which can be 40%, 41%, 43%, 45%, 48%, 50%, 52%, 56%, 59%, 60%, 63%, 64%, 66%, 67%, 70% or any value between 40% and 70%, which is not limited here. When it is within this range, it is convenient to increase the density of the titanium alloy to the required density range after forging and sintering, so that the titanium alloy has a higher structural strength. Of course, after the mixed powder is encapsulated in the sleeve, the density of the blank can also be made less than the above range, and the density of the titanium alloy rod can be increased in the subsequent forging and sintering process to achieve a similar technical effect.

[0094] Please refer to Figure 6In one embodiment of the present application, after the step of placing the mixed powder in a bag and performing a forming process to obtain a green body, the step further includes:

[0095] Step S23, rotary forging the green body to increase the density of the mixed powder.

[0096] Specifically, the blank is rotary forged in a rotary forging machine equipped with a mold or cavity mold of a certain specification, so as to obtain a high-density titanium alloy with low porosity, high density, uniform organizational structure and better mechanical properties, thereby improving the forging quality and efficiency.

[0097] In one embodiment of the present application, the material of the sheath is titanium.

[0098] In this embodiment, titanium is used as the sheath material to avoid the sheath and the mixed powder from fusing during the sintering process, which may cause impurities to be mixed in and affect the purity of the titanium alloy. In addition, if the sheath material needs to be removed, the titanium sheath can be easily processed and removed.

[0099] Please refer to Figure 7 In one embodiment of the present application, the step of rotary forging the blank to increase the density of the mixed powder includes:

[0100] Step S231, rotary forging the green body to make the density of the mixed powder reach 80%-98%.

[0101] Specifically, when the titanium alloy rod is made by rotary forging or other forging processes, the density of the titanium alloy is increased to 80%-98%, which can be 80%, 81%, 83%, 85%, 88%, 90%, 92%, 94%, 96%, 97%, 98% or any value between 80% and 98%. In this way, the titanium alloy produced has a higher alloy content, and under the preset element mass ratio, the ceramic phase is evenly dispersed in the powder particles atomized by the titanium alloy rod. Preferably, the density of the titanium alloy is not less than 95%.

[0102] Please refer to Figure 8 In one embodiment of the present application, the step of sintering the green body to generate a titanium alloy containing a ceramic phase includes:

[0103] The sintering temperature is controlled to be 800° C. to 1400° C., the sintering time is 10 min to 120 min, the sintering atmosphere is at least one of vacuum, argon or nitrogen, and the green body is sintered to generate a ceramic phase in situ and to produce a titanium alloy with a density of not less than 95%.

[0104] In this embodiment, when the forged titanium alloy rod is sintered, it is necessary to sinter the titanium alloy rod in a specific atmosphere or vacuum to avoid oxidation of the titanium alloy and the material, thereby generating a ceramic phase and obtaining a titanium alloy with a desired structure. The sintering temperature can be controlled at 800°C to 1400°C, and the sintering time can be controlled at 10min-120min according to the different materials and proportions added. The sintering atmosphere needs to be controlled to be vacuum, argon, or nitrogen according to the types of carbon, boron, and nitrogen contained in the mixed powder. For example, if a ceramic phase including nitrides needs to be generated, nitrogen needs to be included in the mixed powder. At this time, it needs to be processed under a vacuum or nitrogen sintering atmosphere.

[0105] In one embodiment of the present application, when at least one material of graphite and boron is added to the mixed powder, the sintering temperature is controlled to be 800°C-1400°C, the time is 30min-180min, and the sintering atmosphere is a vacuum degree not exceeding 1×10 -1 Pa vacuum or argon gas with a purity of not less than 99.99% to produce a titanium alloy rod whose ceramic phase is carbide, boride or a composite containing carbide and boride.

[0106] Specifically, if the ceramic phase of the titanium alloy rod is required to contain carbides but not nitrides, pure graphite powder or compound powder should be added to the mixed powder. If the ceramic phase of the titanium alloy rod is required to contain borides but not nitrides, pure boron powder or compound powder should be added to the mixed powder. At this time, the sintering atmosphere can be controlled to have a vacuum degree not exceeding 1×10 -1 Pa vacuum environment or argon environment with purity not less than 99.99%, control the sintering time to 30min-180min, and the sintering temperature to 800℃-1400℃, then the corresponding ceramic phase can be contained in the final titanium alloy rod.

[0107] In one embodiment of the present application, a nitrogen-containing compound is added to the mixed powder, and the sintering process adopted has a sintering temperature of 800°C-1400°C, a sintering time of 30min-180min, and a sintering atmosphere of nitrogen with a purity of not less than 99.99% to produce a titanium alloy rod containing nitride in the ceramic phase.

[0108] Specifically, if the ceramic phase of the titanium alloy rod is required to contain nitride, a nitrogen-containing compound powder needs to be added to the mixed powder. At this time, the sintering atmosphere can be controlled to be a nitrogen environment with a purity of not less than 99.99%, the sintering time can be controlled to be 30min-180min, and the sintering temperature can be controlled to be 800℃-1400℃, so that the ceramic phase of the final titanium alloy rod can contain nitride.

[0109] In some embodiments, when graphite, boron, or a composite containing graphite and boron, and a nitrogen-containing compound are added to the mixed powder, the sintering process uses a sintering temperature of 800°C-1400°C, a sintering time of 30min-180min, and a sintering atmosphere of nitrogen with a purity of not less than 99.99%, then a titanium alloy rod containing at least one of a carbide and a boride and a nitride ceramic phase can be produced.

[0110] The present application also proposes a titanium alloy, which is prepared by the preparation method of the titanium alloy in any of the aforementioned embodiments, and the titanium alloy includes at least one ceramic phase of carbide, boride and nitride. The specific implementation method of the preparation method of the titanium alloy refers to any of the aforementioned embodiments, which will not be repeated here. Since the titanium alloy adopts all the technical solutions of all the aforementioned embodiments, it has at least all the beneficial effects brought by all the technical solutions of all the aforementioned embodiments, which will not be repeated here one by one.

[0111] The present application also proposes a titanium alloy rod, which includes the titanium alloy in the above-mentioned embodiment. Among them, the titanium alloy rod can be obtained by directly firing a rod-shaped titanium alloy structure using the above-mentioned titanium alloy preparation method, or the titanium alloy raw material can be first obtained and then the required titanium alloy rod can be machined, which is not limited here; in addition, it should be noted that when the above-mentioned preparation method is directly used, the titanium alloy rod obtained after the sintering process may still not be directly used for the atomization process to prepare titanium alloy powder in terms of size and shape. The sintered titanium alloy rod can be surface treated or machined to trim its shape, size and surface structure characteristics to a titanium alloy rod that meets the atomization process. For example, the titanium alloy rod can be polished, sandblasted, cut, etc., so that it meets the shape and size requirements of electrode induction melting gas atomization method or plasma rotating electrode method.

[0112] Since the titanium alloy rod adopts all the technical solutions of all the aforementioned embodiments, it at least has all the beneficial effects brought by all the technical solutions of all the aforementioned embodiments, which will not be described one by one here.

[0113] In order to further understand the present invention, the preparation method of the titanium alloy provided by the present invention is specifically described below in conjunction with embodiments.

[0114] In the first embodiment of the present application for preparing a titanium alloy rod, a titanium alloy rod is designed whose raw material composition includes titanium and 5% aluminum, 5% vanadium, 5% molybdenum, 1% iron, 1% chromium and 1% carbon in a mass ratio. A pure titanium tube with a diameter of 60 mm, a wall thickness of 1 mm and a length of 500 mm is selected as the sheath. The mass of the titanium tube is calculated to be 417.8 grams, and the total mass of the powder is 2640.7 grams.

[0115] Specifically, titanium powder, aluminum powder, vanadium powder, molybdenum powder, iron powder, chromium powder, and graphite powder are mixed in a ratio of 79.15:5.79:5.79:5.79:1.16:1.16:1.16 (mass percentage), mixed for 45 minutes, and then 1% epoxy resin is added as a binder, heated to 100-120°C for another 50 minutes, then cooled, taken out, crushed, and passed through a 20-mesh sieve to obtain a uniformly mixed bonding powder. One end of the pure titanium tube is flattened and sealed, and then the bonding powder is loaded, and the other end of the titanium tube is flattened after vibration. The titanium tube filled with powder is then forged, and the outer diameter gradually becomes 45mm, with a density of about 85%. Then, an air outlet is opened at the sealed end at the back, and then placed in a vacuum sintering furnace, and the temperature is 1℃ / min between room temperature and 700℃, and the temperature is kept at 700℃ for 30min; then the temperature is raised to 1300℃ at a rate of 5℃ / min, and the temperature is kept for 60min. After cooling, a titanium alloy rod containing a carbide ceramic phase is prepared, and the density is 95.5%. The sintered titanium alloy rod is sandblasted on the surface and atomized by EIGA (electrode induction melting gas atomization method) to form a powder, and the ceramic phase is distributed inside the particles and dispersed evenly.

[0116] In the second embodiment of the present application for preparing a titanium alloy rod, a titanium alloy rod is designed, the raw material composition of which includes titanium and a mass ratio of 5% aluminum, 5% vanadium, 5% molybdenum, 1% iron, 1% chromium and 1% carbon. A pure titanium tube with a diameter of 60 mm, a wall thickness of 1 mm and a length of 500 mm is selected as the sheath. The mass of the titanium tube is calculated to be 417.8 grams, and the total mass of the powder is 2640.7 grams.

[0117] Specifically, titanium powder, AlV50 alloy powder, molybdenum powder, iron powder, chromium powder, and graphite powder are mixed in a ratio of 76.83:13.90:5.79:1.16:1.16:1.16 (mass percentage), put into a stirring mixer, mix for 60 minutes, add 0.5% phenolic resin as a binder, heat to 120-130° C., stir and mix for 50 minutes, then cool and take out for mechanical crushing, pass through a 20-mesh sieve, and obtain a uniformly mixed titanium alloy bonding powder raw material. One end of the pure titanium tube is flattened and sealed, and then the bonding powder is loaded, and the other end of the titanium tube is flattened and sealed after vibration. The titanium tube filled with powder is forged, and the outer diameter gradually becomes 45mm, and the density is about 85%. Then, an air outlet is opened at the sealed end at the back, and then it is placed in a vacuum sintering furnace, with a vacuum degree of ≤0.1Pa, 5℃ / min between room temperature and 700℃, and kept at 700℃ for 30min; then the temperature is raised to 1280℃ at a rate of 3℃ / min, kept for 50min, and cooled to prepare a titanium alloy rod containing carbide ceramic phase, with a density of 95.2%. The sintered titanium alloy rod is sandblasted on the surface and can be used for EIGA atomization to make powder, and the ceramic phase is distributed inside the particles and dispersed evenly.

[0118] In the third embodiment of the present application for preparing a titanium alloy rod, a titanium alloy rod is designed whose raw material composition includes titanium and a titanium alloy rod with a mass ratio of 5% aluminum, 5% vanadium, 5% molybdenum, 1% iron, 1% chromium and 1% carbon. A pure titanium tube with a diameter of 60 mm, a wall thickness of 1 mm and a length of 500 mm is selected as the sheath. The mass of the titanium tube is calculated to be 417.8 grams, and the total mass of the powder is 2640.7 grams.

[0119] Specifically, titanium powder, AlV50 alloy powder, molybdenum powder, iron powder, chromium powder, and graphite powder are mixed in a ratio of 79.15:11.58:5.79:1.16:1.16:1.16 (mass percentage), put into a stirring mixer, mix for 45 minutes, add 0.5% epoxy resin as a binder, heat to 100-120° C., stir and mix for 60 minutes, then cool and take out for mechanical crushing, pass through a 20-mesh sieve, and obtain a uniformly mixed titanium alloy bonding powder raw material. One end of the pure titanium tube is flattened and sealed, and then the bonding powder is loaded, and the other end of the titanium tube is flattened and sealed after vibration. The titanium tube filled with powder is placed in a vacuum sintering furnace with a vacuum degree of ≤0.1Pa, and the temperature is raised from room temperature to 700°C at a heating rate of 4°C / min, and then kept at 700°C for 30 minutes; then the temperature is raised to 1350°C at a heating rate of 3°C / min, kept for 50 minutes, and cooled to prepare a titanium alloy rod containing a carbide ceramic phase with a density of 89.5%. The sintered titanium tube is integrally forged to prepare a titanium alloy rod containing a carbide ceramic phase with a density of 98.2%. The titanium alloy rod after forging is sandblasted on the surface and can be used for EIGA (electrode induction melting gas atomization method) atomization to form powder, and the carbide ceramic phase is distributed inside the particles and dispersed evenly.

[0120] In the fourth embodiment of the present application for preparing a titanium alloy rod, the titanium alloy raw material composition is designed to include titanium and a titanium alloy rod with a mass ratio of 5% aluminum, 5% vanadium, 5% molybdenum, 1% iron, 1% chromium and 1% carbon. A pure titanium tube with a diameter of 60 mm, a wall thickness of 1 mm and a length of 500 mm is selected as the sheath. The mass of the titanium tube is calculated to be 417.8 grams, and the total mass of the powder is 2640.7 grams.

[0121] Specifically, titanium powder, AlV50 alloy powder, molybdenum powder, iron powder, chromium powder, and graphite powder are mixed in a ratio of 79.15:11.58:5.79:1.16:1.16:1.16 (mass percentage), put into a stirring mixer, mix for 45 minutes, add 0.5% epoxy resin as a binder, heat to 100°C-120°C, stir and mix for 60 minutes, then cool and take out for mechanical crushing, pass through a 20-mesh sieve, and obtain a uniformly mixed titanium alloy bonding powder raw material. One end of the pure titanium tube is flattened and sealed, and then the bonding powder is loaded, and the other end of the titanium tube is flattened and sealed after vibration. The titanium tube filled with powder is placed in an atmosphere sintering furnace, with nitrogen as the protective gas, and the temperature is raised from room temperature to 700°C at a heating rate of 4°C / min, and then kept at 700°C for 30 minutes; then the temperature is raised to 1300°C at a heating rate of 3°C / min, kept for 50 minutes, and after cooling, a titanium alloy rod containing two ceramic phases of nitride and carbide is prepared, with a density of 87%. The sintered titanium tube is rotary forged to prepare a titanium alloy rod containing nitride and carbide ceramic phases, with a density of 97.5%. The titanium alloy rod after rotary forging is sandblasted on the surface, and can be used for EIGA (electrode induction melting gas atomization method) atomization to form powder, and the nitride and carbide ceramic phases are distributed inside the particles and are evenly dispersed.

[0122] In the fifth embodiment of the present application for preparing a titanium alloy rod, the titanium alloy raw material composition is designed to include titanium and a titanium alloy rod with a mass ratio of 5% aluminum, 5% vanadium, 5% molybdenum, 1% iron, 1% chromium, 0.5% carbon and 0.5% boron. A pure titanium tube with a diameter of 60 mm, a wall thickness of 1 mm and a length of 500 mm is selected as the sheath. The mass of the titanium tube is calculated to be 417.8 grams, and the total mass of the powder is 2640.7 grams.

[0123] Specifically, titanium powder, AlV50 alloy powder, molybdenum powder, iron powder, chromium powder, graphite powder, and boron powder are mixed in a ratio of 79.15:11.58:5.79:1.16:1.16:0.58:0.58 (mass percentage), put into a stirring mixer, mix for 45 minutes, add 0.5% epoxy resin as a binder, heat to 100-120°C, stir and mix for 60 minutes, then cool and take out for mechanical crushing, pass through a 20-mesh sieve, and obtain a uniformly mixed titanium alloy bonding powder raw material. One end of the pure titanium tube is flattened and sealed, and then the bonding powder is loaded, and the other end of the titanium tube is flattened and sealed after vibration. The titanium tube filled with powder is placed in an atmosphere sintering furnace, and nitrogen is used as a protective gas. The temperature is raised from room temperature to 700°C at a heating rate of 4°C / min, and then kept at 700°C for 30 minutes; then the temperature is raised to 1300°C at a heating rate of 3°C / min, and kept at 700°C for 50 minutes. After cooling, a titanium alloy rod containing three ceramic phases of carbide, boride and nitride is prepared, and the density is 86.5%. The sintered titanium tube is rotary forged to prepare a titanium alloy rod containing carbide, boride and nitride ceramic phases, and the density reaches 97.3%. The titanium alloy rod after rotary forging is sandblasted on the surface, and can be used for EIGA (electrode induction melting gas atomization method) atomization to make powder, and the carbide, boride and nitride ceramic phases are distributed inside the particles and are evenly dispersed.

[0124] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for preparing a titanium alloy, characterized in that: include: Mixing a base powder containing titanium elements with a reinforcing powder containing alloy elements to form a mixed powder, wherein the alloy elements include metal elements and non-metal elements, the metal elements include at least one of aluminum, vanadium, molybdenum, chromium, and iron, and the non-metal elements are at least one of carbon, boron, and nitrogen; Forming the mixed powder into a green body to obtain a green body; The green body is sintered to produce a titanium alloy containing a ceramic phase.

2. The method for preparing a titanium alloy according to claim 1, characterized in that: The mass ratio of each element in the mixed powder is: Aluminum 4% to 6%; Vanadium 4% to 6%; Molybdenum 4% to 6%; Iron 0.5% to 1.5%; Chromium 0.5% to 1.5%; At least one of carbon, boron and nitrogen 0.5% to 1.5%; The balance is titanium.

3. The method for preparing a titanium alloy according to claim 1, characterized in that: The matrix powder includes at least one of titanium powder and titanium alloy powder.

4. The method for preparing a titanium alloy according to claim 1, characterized in that: The step of mixing the matrix powder containing titanium element and the reinforcing powder containing alloy element to form mixed powder comprises: Adding a binder to the base powder and the reinforcing powder and heating and mixing them to obtain a mixture; wherein the binder includes at least one of epoxy resin, phenolic resin, and rubber; After the mixture is cooled, it is crushed to obtain mixed powder; Alternatively, the step of mixing the matrix powder containing titanium element and the reinforcing powder containing alloy element to form a mixed powder comprises: Adding liquid to the base powder and the reinforcing powder and mixing them to obtain a mixture; wherein the liquid includes at least one of liquid epoxy resin, liquid phenolic resin, acetone epoxy resin solution, ethyl acetate epoxy resin solution, acetone phenolic resin solution, ethanol phenolic resin solution, ethanol, ethyl acetate, acetone, gasoline rubber solution, engine oil, and gasoline; The mixed material is dried to obtain mixed powder.

5. The method for preparing a titanium alloy according to claim 4, characterized in that: The mass percentage of the binder to the mixed powder is 0.1% to 5.0%.

6. The method for preparing a titanium alloy according to claim 1, characterized in that: The step of forming the mixed powder into a green body to obtain a green body comprises: The mixed powder is placed in a bag and subjected to a forming process to obtain a green body.

7. The method for preparing a titanium alloy according to claim 6, characterized in that: The step of placing the mixed powder in the bag and performing a forming process to obtain a green body comprises: The mixed powder is placed in a bag, and after compaction, the bag is vacuum-sealed to form a green body.

8. The method for preparing a titanium alloy according to claim 6, characterized in that: After the step of placing the mixed powder in the bag and performing a forming process to obtain a green body, the step further includes: The green body is rotary forged to increase the density of the mixed powder.

9. The method for preparing a titanium alloy according to claim 8, characterized in that: The step of rotary forging the blank to increase the density of the mixed powder comprises: The green body is rotary forged to make the density of the mixed powder reach 80%-98%.

10. The method for preparing a titanium alloy according to claim 8, characterized in that: The material of the sheath is titanium.

11. The method for preparing a titanium alloy according to any one of claims 1 to 10, characterized in that: The step of sintering the green body to generate a titanium alloy containing a ceramic phase comprises: The sintering temperature is controlled to be 800° C. to 1400° C., the sintering time is 10 min to 120 min, the sintering atmosphere is at least one of vacuum, argon or nitrogen, and the green body is sintered to generate a ceramic phase in situ and to produce a titanium alloy with a density of not less than 95%.

12. A titanium alloy, characterized in that: The titanium alloy is prepared by the method for preparing the titanium alloy as claimed in any one of claims 1 to 11, and the titanium alloy includes at least one ceramic phase selected from carbide, boride and nitride.

13. A titanium alloy rod, characterized in that: Comprising the titanium alloy as claimed in claim 12.